Pertumbuhan dan Produksi Sorgum bicolor pada Kultur Fungi Mikoriza Arbuskula (FMA) dengan Sistem Fertigasi dan Fortifikasi Nutrisi Berbeda: Growth and Production of Sorghum bicolor in Arbuscular Mycorrhizal Fungi (AMF) Cultures with Different Fertigation and Nutrient Fortification Systems - Ana Fitria; L Abdullah; P D M H Karti (Jurnal Ilmu Nutrisi dan Teknologi Pakan (Nutrition and Feed Technology Journal), 2022)
Arbuscular mycorrhizal Fungi (AMF) is a microorganism that biologically affects plant enzymes and plant nutrients. AMF production development techniques need to be improved with the addition of nutritional fortification to produce quality AMF products. The research aimed was to cultivate AMF with complete fertilizer nutrition and different fertigation systems on Sorghum bicolor. The study used a 2 x 3 factorial randomized design with A factor: fertigation system (flat and terraced) and B factor: fertilizer nutrient levels (1000ppm, 2000ppm, 3000ppm). The results showed that the flat fertigation system had a significant different (p<0.05) on plant height, the number of leaves, stem diameter, and fresh biomass. However, in the high-level fertigation system, numbers of leaf, stem diameter, and fresh biomass did not have significant difference. There was no interaction between the fertigation and nutrient fortification systems. Sorghum panicle age started at 75 yields after planting (DAT). The relationship between percent infection and the number of spores showed a low level of correlation with R2 = 0.032. It can be concluded that the best fertigation system was a flat fertigation system for all nutrient fortifications, with the best average yield on 2000ppm nutrient fortification. Key words: AMF, fertigation system, nutrition fortification